Evaluasi Pelaksanaan Peradilan Daring Di Pengadilan Agama Jakarta Selatan Untuk Mengoptimalisasi Penyelesaian Perkara Perceraian Selama Pandemi Covid-19 - Susetyo, Heru; Febriyanto, Satrio Alif; Kardinal, Rosalinda Estevani (Jurnal Hukum & Pembangunan, 2022)
To facilitate judicial process implementation during the COVID-19 Pandemic, courts can be conducted online. Besides preventing mass gatherings that avoid during the COVID-19 Pandemic, online courts also have other benefits to shortening time and saving court costs. The study of online justice application at the South Jakarta Religious Courts aims to find out online justice application in the divorce cases settlement with the final result of an online justice application evaluation in the divorce cases settlement during the COVID-19 Pandemic that can be used as evaluation material for stakeholders so that online courts can conduct better in the future. The research method used is juridical-normative through the literature and legislation studies related to divorce, lawsuits, online courts, and case data at the South Jakarta Religious Court. Based on the research result, the implementation of justice at the South Jakarta Religious Court has reflected the state presence in providing legal certainty for citizens in the jurisdiction of South Jakarta through the judicial process implementation during the COVID-19 Pandemic continues to run smoothly. However, the reality of online courts often experiences several obstacles, so a thorough implementation evaluation and its impact on the ongoing judicial process is required.